Integrating Academic Supervision, Transformational Leadership, and Islamic Organizational Culture to Enhance Graduate Quality - Rahayuningsih, Puji; Diana, Nirva; Warisno, Andi (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study examines how academic supervision operates within Islamic organizational culture through transformational leadership and how this interaction contributes to graduate quality in Islamic Integrated Junior High Schools in North Lampung Regency, Indonesia. Although academic supervision, transformational leadership, and organizational culture have been widely discussed in educational leadership literature, limited qualitative evidence explains how these three dimensions interact within faith-based junior high schools to shape graduate quality. Employing a qualitative multi-site case study design, data were collected from nine schools through semi-structured interviews, non-participant observations, and document analysis involving principals, vice principals, and teachers. Thematic analysis utilizing NVivo 14 software revealed that schools implementing developmental academic supervision supported by transformational leadership and internalized Islamic organizational values demonstrate stronger instructional coherence and higher graduate progression outcomes, with progression rates to elite senior secondary schools ranging from 30% to 35% in high-performing institutions. In contrast, supervision oriented toward administrative compliance shows limited impact on instructional improvement. The study highlights that graduate quality is shaped not only by academic achievement but also by the alignment of leadership, supervision, and organizational culture. These findings contribute to instructional leadership literature by offering an integrative perspective within a faith-based educational context. Practically, the study implies that strengthening graduate quality requires dialogical supervision and leadership development programs that align professional learning with organizational values.